On an approach to construction the basic of nanomaterials mechanics - Nahirnyi, T.; Tchervinka, K. (Фізико-математичне моделювання та інформаційні технології, 2010)
In the paper the basic relations for description of elastic deformation of nanoporous solids are proposed. They include a classical equilibrium equation and a constitutive relation between stress and strain tensors. While formulating the latter it is assumed that elastic moduli can be presented as a product of two functions. The first one depends on characteristic size of the nanoscale elements forming material, the second depends on the porosity coefficient. For description of the elastic moduli dependence on characteristic size the local gradient approach in thermomechanics is used. On the base of the model problems solutions for a layer and a cylinder there are investigated the nanoscale element geometry and size influences on elastic moduli, including Young modulus and Poisson coefficient. У роботі запропоновано основні співвідношення для опису пружного деформування нанопористих тіл. Вони включають класичне рівняння рівноваги та визначальне співвідношення, що пов’язує тензори напружень і деформації. Під час формулювання останнього прийнято, що пружні модулі можна подати у вигляді добутку двох функцій. Перша із них залежить від характерного розміру наноелементів, що утворюють наноматеріал, тоді як друга — від коефіцієнта пористості. Для опису залежності пружних модулів від характерного розміру використано локально градієнтний підхід у термомеханіці. На основі модельних задач для шару та циліндра досліджено вплив геометрії та розміру наноелемента на величину пружних модулів матеріалу, включаючи модуль Юнга та коефіцієнт Пуассона. В работе предложены основные соотношения для описания упругой деформации нанопористых тел. Они включают классическое уравнение равновесия и определяющее соотношение между тензорами напряжений и деформаций. При формулировке последнего принято, что упругие модули можно представить в виде произведения двух функций. Первая из них зависит от характерного размера наноелементов, образующих наноматериал, тогда как вторая — от коэффициента пористости. Для описания зависимости упругих модулей от характерного размера использован локально градиентный подход в термомеханике. На основе модельных задач для слоя и цилиндра исследовано влияние геометрии и размера наноелемента на величину упругих модулей материала, включая модуль Юнга и коэффициент Пуассона.